Female Journalists in the Digital Media Platform Environment - Wardatul Jannah (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
This research aims to explore the challenges faced by female journalists in the digital space, and to examine the safety threats they encounter, including online gender-based violence (OGBV), cyber trolling, and harassment. The study will also investigate the strategies employed by both female journalists and media organizations to address these issues. A mixed-methods approach will be used, qualitative methods. The qualitative data will be collected through in-depth document analysis of media safety protocols. The study will focus on digital space, which has not been extensively researched in terms of gender-based violence in journalism. By identifying the unique experiences and safety challenges faced by female journalists in this region, the research aims to contribute to a deeper understanding of the issue and provide recommendations for improving safety measures and gender-specific protection strategies. This research will offer valuable insights for media organizations globally in addressing the digital safety of female journalists and ensuring their well-being both online and offline.